2022
DOI: 10.1097/mco.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Do omega-3 fatty acids increase risk of atrial fibrillation?

Abstract: Purpose of the reviewTo summarize the findings from recent observational follow-up studies and randomized trials of plant- and marine omega-3 fatty acids on the risk of atrial fibrillation (AF).Recent findingsRecent randomized cardiovascular outcome trials have indicated that supplements with marine omega-3 fatty acids may be associated with a higher risk of AF, and a meta-analysis has suggested that marine omega-3 fatty acid supplements were associated with a 25% higher relative risk of AF. Also, a recent lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Clinical and experimental studies have shown that EPA and DHA supplementation may affect the stabilization of cardiomyocyte cell membranes by affecting ion channel proteins, which is crucial for proper cardiac electrophysiology. EPA and DHA can modulate the activity of sodium and potassium channels, which affects the length of the cardiac functional potential and the refractivity of the heart muscle, thereby reducing susceptibility to proarrhythmic conduction disorders [6,7,8].…”
Section: A) Omega-3 Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and experimental studies have shown that EPA and DHA supplementation may affect the stabilization of cardiomyocyte cell membranes by affecting ion channel proteins, which is crucial for proper cardiac electrophysiology. EPA and DHA can modulate the activity of sodium and potassium channels, which affects the length of the cardiac functional potential and the refractivity of the heart muscle, thereby reducing susceptibility to proarrhythmic conduction disorders [6,7,8].…”
Section: A) Omega-3 Fatty Acidsmentioning
confidence: 99%
“…Other studies have shown no statistically significant benefit of omega-3 supplementation in the prevention or treatment of AF. Such discrepancies may be due to differences in dosages, duration of supplementation, characteristics of study populations and different supplement formulations [7][8][9][10][11].…”
Section: A) Omega-3 Fatty Acidsmentioning
confidence: 99%
“…Although no studies are available in patients with lipodystrophies, a previous large-scale clinical study (68) reported cardiovascular benefits in patients with fasting triglyceride levels of 135-499 mg/dL following treatment with icosapent ethyl. However, the use of these agents may be limited in patients with lipodystrophies who are at higher risk of developing arrhythmias, as an increased risk of atrial fibrillation has been reported after the use of omega-3 fatty acids, particularly in high doses (69)(70)(71).…”
Section: Management Of Lipid Abnormalities With Standard Approachesmentioning
confidence: 99%
“…A meta-analysis suggests that supplemental long chain n-3 PUFAs increase risk of atrial fibrillation [25], and a recent large observational study reported a modestly increased risk of atrial fibrillation in habitual users of n-3 PUFA supplements [26]. Bork et al [24] discuss candidate mechanisms for this potential adverse effect of n-3 PUFAs.…”
mentioning
confidence: 99%
“…Nevertheless, and despite showing an overall benefit on mortality, some trials report an increased risk of atrial fibrillation with long chain n-3 PUFAs [23]. Bork et al [24] discuss this further. A meta-analysis suggests that supplemental long chain n-3 PUFAs increase risk of atrial fibrillation [25], and a recent large observational study reported a modestly increased risk of atrial fibrillation in habitual users of n-3 PUFA supplements [26].…”
mentioning
confidence: 99%